A non-enzymatic sensor for sensitive determination of H2O2 using biomimetic nanocomposite - Mukherjee, Atripan; Ashrafi, Amirmansoor; Richtera, Lukáš; Adam, Vojtěch (Mendel University in Brno, 2019)
Hydrogen peroxide (H2O2), as a critical secondary messenger, is important for in vitro and in vivo study. In addition, it is of great significance in monitoring the biological condition under chemical oxidative stress. A non-enzymatic sensor was developed for the detection and monitoring of H2O2 using a nanocomposite (NC). The NC is prepared and modified by using multi-walled carbon nanotubes and tris(2,2’-bipyridyl) copper(II) dichloride complex acts as a mediator. The electrochemical techniques like cyclic voltammetry and chrono-amperometry were used to study the electrochemical behaviour of H2O2 at the developed electrode. The reduction peak of H2O2 shifts to less negative potential with increasing the reducing current at the developed electrode. The calibration curve of the proposed sensor was plotted using chrono-amperometry at 0.1 V as applied potential with stepwise addition of H2O2. The developed sensor has high stability and able to detect H2O2 with a high sensitivity and repeatability. The linear range was found to be 2.4–33.0 µg/ml. Furthermore, the limit of detection and the limit of quantification were 0.7 µg/ml and 2.4 µg/ml, respectively. The reproducibility of the prepared sensor was evaluated by calculating the RSD% = 7.2.

Hydrogen peroxide (H2O2), as a critical secondary messenger, is important for in vitro and in vivo study. In addition, it is of great significance in monitoring the biological condition under chemical oxidative stress. A non-enzymatic sensor was developed for the detection and monitoring of H2O2 using a nanocomposite (NC). The NC is prepared and modified by using multi-walled carbon nanotubes and tris(2,2’-bipyridyl) copper(II) dichloride complex acts as a mediator. The electrochemical techniques like cyclic voltammetry and chrono-amperometry were used to study the electrochemical behaviour of H2O2 at the developed electrode. The reduction peak of H2O2 shifts to less negative potential with increasing the reducing current at the developed electrode. The calibration curve of the proposed sensor was plotted using chrono-amperometry at 0.1 V as applied potential with stepwise addition of H2O2. The developed sensor has high stability and able to detect H2O2 with a high sensitivity and repeatability. The linear range was found to be 2.4–33.0 µg/ml. Furthermore, the limit of detection and the limit of quantification were 0.7 µg/ml and 2.4 µg/ml, respectively. The reproducibility of the prepared sensor was evaluated by calculating the RSD% = 7.2.
A non-enzymatic sensor for sensitive determination of H2O2 using biomimetic nanocomposite
Keywords: non-enzymatic; nanocomposite; biomimetic; nanozymes; sensors; non-enzymatic; nanocomposite; biomimetic; nanozymes; sensors